2014
DOI: 10.2528/pierl14101601
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation on the Use of Itu-R P.1411-7 in 802.11N Path Loss Modelling

Abstract: Abstract-Free space path loss modelling is a model used to model path loss propagation for Wireless Local Area Networks. In some cases, the estimation of path loss by the FSL model can be inaccurate as it does not take into account the effects of multipath propagation. The International Telecommunication Union Recommendation, ITU-R P.1411-7 provides prediction methods for the planning of short-range outdoor radio communication systems and radio local area networks in the frequency range of 300 MHz to 100 GHz. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Past works in [6][7][8] have used the ITU-R P.1411-7 recommendation [9] to predict path loss of local area networks. Recently, field experiments done in [10] have shown that ITU-R P.1411-7 can predict path loss in a suburban environment with higher accuracy than the FSPL.…”
Section: Introductionmentioning
confidence: 99%
“…Past works in [6][7][8] have used the ITU-R P.1411-7 recommendation [9] to predict path loss of local area networks. Recently, field experiments done in [10] have shown that ITU-R P.1411-7 can predict path loss in a suburban environment with higher accuracy than the FSPL.…”
Section: Introductionmentioning
confidence: 99%